The enhanced degradation behavior of oxytetracycline by black soldier fly larvae with tetracycline resistance genes in the larval gut: Kinetic process and mechanism - Liu, Cuncheng; Yao, Huaiying; Cao, Qingcheng; Wang, Tielin; Wang, Cunwen (Environmental research, 2022)
Black soldier fly larvae (larvae) can digest organic wastes and degrade contaminants such as oxytetracycline (OTC). However, compared to the kinetic processes and enhanced mechanisms used in the traditional microbial degradation of OTC, those employed by larvae are largely uncharacterized. To obtain further details, a combined analysis of larval development, larval nutritional values (crude protein, crude fat and the composition of fatty acids) and the expression of tetracycline resistance genes (TRGs) in the larval gut was performed for the degradation of OTC added to substrates and for oxytetracycline bacterial residue (OBR). When the larvae were exposed to the substrates, the degradation processes were enhanced significantly (P < 0.01), with a 4.74–7.86-fold decrease in the degradation half-life (day−1) and a 3.34–5.74-fold increase in the final degradation efficiencies. This result was attributed to the abundant TRGs (with a detection rate of 35.90%∼52.14%) in the larval gut. The TRGs presented the resistance mechanisms of cellular protection and efflux pumps, which ensured that the larvae could tolerate elevated OTC concentrations. Investigation of the TRGs indicated that enzymatic inactivation enhanced OTC degradation by larvae. These findings demonstrate that the larval degradation of antibiotic contaminants is an efficient method based on abundant TRGs in the larval gut, even though OTC degradation results in OBR. In addition, a more optimized system for higher reductions in antibiotic levels and the expansion of larval bioremediation to other fields is necessary. •Oxytetracycline can be degraded effectively by Hermetia illucens.•The kinetic character and degradation mechanism of oxytetracycline were explored.•TRGs in larval guts play a key role in the oxytetracycline degradation.